Self-rhythm of the Belenoby Poet (Journal of the College of Languages (JCL), 2019)
Al- belenoby , Andalusian obscure poet .I choose to study poetic rhythm in this poetic and the appropriateness of with what rhythm touring in his self to give beautiful meaning raise to receiver to put the hands of continental placements creativity in poetry .I divided my research into ideas are presented in a sequential manner , I started researching with poetic rhyme than rhyme they represent the form of the poem, they represent the external form of the poem and their music that farm the general concept then the rhetorical styles that represent the internal form of the poem and it music that the listener works and enjoying it part by part all this led to the put the hands of the receiver placement creativity in Belenoby Poet.